WARISAN PATRIARKI: HAMBATAN STRUKTURAL BAGI PEREMPUAN DI DUNIA KERJA - Prhita Shintiya; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
Patriarchal culture remains a major factor contributing to gender inequality across various aspects of life, particularly in the workplace. This social system positions men as the dominant group, while women are often placed in subordinate roles that limit their mobility and opportunities for growth. In professional settings, women face numerous structural barriers, ranging from discrimination in recruitment and wage gaps to limited access to leadership roles or strategic positions. Moreover, social expectations that place domestic responsibilities on women further burden them and restrict their participation in the professional sphere. Gender-based discrimination also frequently manifests in the form of stereotypes, disregard for contributions, and a lack of institutional policy support for equality. These issues create persistent disparities and hinder the full realization of women’s potential. This study aims to analyze the impact of the patriarchal cultural legacy on women's career development and to explore strategies, approaches, and policies that can foster a more just, equitable, and inclusive work environment for all.